Peran Orang Tua Dalam Perkembangan Ketrampilan Awal Literasi Anak - Hafidz Triantoro Aji Pratomo; Muryanti Muryanti (Poltekkes Kemenkes Surakarta, 2020)
Background: Literacy is a supporting component of children's academic success. Literacy ability is influenced by interdependent language skills. Limitations on early literacy skills increase the chance of academic process obstacles at school age. The role of parents is crucial in the child's development process especially in literacy. Aim this study is to describe correlation between parental variabels and early literacy skills. Methods: This cross sectional research was conducted with a survey approach. The instrument was developed to explore demographic information, socioeconomic status, and the role of parents in developing early literacy skills. Statistic descriptive and correlation study was conducted to analyse 180 respondent data. Results: The role of parents has contributed to the development of early literacy skills. Parental history, mother's education, and language activities have a positive relationship with the development of early literacy skills. Conclusions: The role of parents is one of the multivariate variables that play a role in the development of early literacy skills. Further search is needed to see the extent of the role of parents in carrying out specific activities that are relevant to children's literacy abilities.